2021
DOI: 10.12912/27197050/137867
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Implications of the Dynamics of Water Volume Growth in a Reservoir

Abstract: The rate of growth of the water volume in the reservoir varies with each charging season. The accuracy of the predictions is required in sustainable reservoir management. Its intrinsic growth rate as an ecological parameter plays a role in determining this speed. This study aimed to analyze the dynamics of water volume growth based on its intrinsic growth rate to assess the potential for hydrometeorology disasters. The population growth models proposed to be tested for suitability and goodness is the Verhulst,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Furthermore, Waliszewski [15] showed that the derivative of the Gompertz function is a PDF, and the probability distribution of it is a solution of non-Gaussian form. The Verhulst, Richards, Comperzt, and modified Malthus model were used to to understand the dynamics of water volume growth in a reservoirs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Waliszewski [15] showed that the derivative of the Gompertz function is a PDF, and the probability distribution of it is a solution of non-Gaussian form. The Verhulst, Richards, Comperzt, and modified Malthus model were used to to understand the dynamics of water volume growth in a reservoirs [5].…”
Section: Introductionmentioning
confidence: 99%